Temperature Dependence of Hard Carbon Performance in Sodium Half-Cells with 1 M NaClO4 in EC/DEC Electrolyte - Bowen Liu; Andrew L. Hector; Weronika O. Razmus; Richard G. A. Wills (Batteries, 2022)
In recent years, sodium-ion batteries (SIBs) have attracted much attention as an alternative to lithium-ion batteries. Hard carbon (HC) is a well-studied anode material for SIBs; however, the performance as a function of temperature is less established. To investigate temperature dependence of the performance of HC, sodium half-cells with a common NaClO4-based electrolyte were tested at temperatures from 10 to 80 °C. Capacity after 20 cycles at 100 mA g−1 current varied from 90 mA h g−1 at 10 °C to 270 mA h g−1 at 60 °C. Increased temperature significantly improves the HC rate capability, with 120 mA h g−1 capacity found at 60 °C with 500 mA g−1 current. Stability was high at moderate temperature with 220 mA h g−1 capacity remaining after 200 cycles at 40 °C with a current of 100 mA g−1.